2015
DOI: 10.1002/ppul.23356
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium in cystic fibrosis—Systematic review of the literature

Abstract: The first comprehensive review of the literature confirms that, despite being one of the most prevalent minerals in the body, the importance of magnesium in cystic fibrosis is largely overlooked. In these patients, hypomagnesemia should be sought once a year. Furthermore, the potential of supplementation with this cation deserves more attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…LadS is stimulated by high calcium in the extracellular milieu (Broder et al, 2016). Further, recent work (Chakravarty et al, 2017) has reported that the inner membrane magnesium transporter MgtE, whose own expression is augmented during antibiotic pressure (Redelman et al, 2014) and low magnesium (both signals present in CF airway) (Coffey et al, 2014; Santi et al, 2016), signals through GacS to increase rsmYZ transcription. GacAS thus represents a hub of environmental regulation of the Rsm signaling.…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
“…LadS is stimulated by high calcium in the extracellular milieu (Broder et al, 2016). Further, recent work (Chakravarty et al, 2017) has reported that the inner membrane magnesium transporter MgtE, whose own expression is augmented during antibiotic pressure (Redelman et al, 2014) and low magnesium (both signals present in CF airway) (Coffey et al, 2014; Santi et al, 2016), signals through GacS to increase rsmYZ transcription. GacAS thus represents a hub of environmental regulation of the Rsm signaling.…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
“…deficiency is reported in patients with cystic fibrosis and is mainly due to four reasons; insufficient dietary intake, reduced intestinal absorption (due to pancreatic insufficiency associated with the disease), hyperglycemia associated with cystic fibrosis may trigger hypomagnesaemia and renal wasting associated with intake of drugs like b 2 agonists, thiazides, loop diuretics, calcineurin inhibitor, amino-glycoside antibiotics etc. (Lee et al 2015;Santi et al 2016). Recombinant human DNase is used for treatment purposes, and magnesium is essential for its activation (Santi et al 2016).…”
Section: Cystic Fibrosis Cystic Fibrosis Is An Autosomal Recessive Disorder Due To Mutation In the Cftr (Cystic Fibrosis Transmembrane Comentioning
confidence: 99%
“…(Lee et al 2015;Santi et al 2016). Recombinant human DNase is used for treatment purposes, and magnesium is essential for its activation (Santi et al 2016). Therefore the efficiency of the treatment is related to the Mg 2?…”
Section: Cystic Fibrosis Cystic Fibrosis Is An Autosomal Recessive Disorder Due To Mutation In the Cftr (Cystic Fibrosis Transmembrane Comentioning
confidence: 99%
See 1 more Smart Citation
“…Studies addressing the intracellular magnesium concentration and the kidney magnesium handling were also included. Chronic alcohol-use disorder subjects in treatment with drugs with a potential to cause hypomagnesemia such as aminoglycosides, calcineurin inhibitors, diuretics, or proton-pump inhibitors were excluded [4,7,8].…”
Section: Selection Criteriamentioning
confidence: 99%